Physical Informal Learning Environment on Campus Ground: A Review - V., Ramu; Taib, Nooriati; Aziz, Nor Fadzila (School of Social Sciences, USM, 2017)
Past few decades, there has been a raft amplifying interest in higher education institutions, nationally and internationally, in the creation of new types of learning environment supporting learner-centered or constructivist pedagogy. This paper reviews the effectiveness of the physical informal learning environment initiated by learners outside their formal lecture hours in higher education. The aim of this paper is to present a synthesis of 40 studies from 1979 to 2016 on pyhsical informal learning setting on campus. Learning is the essential activity of colleges and universities. Commonly learning occurs in classrooms which identified as formal learning and sometimes its results from serendipitous interactions among individuals at transitional spaces which classified as informal learning. Space whether physical or virtual can have an impact on learning. Thus, it can bring people together, encourage exploration, collaboration, and discussion. Space can carry an unspoken message of silence which mentioned as the power of built pedagogy in colleges and universities. Nevertheless, the subject remains topical due to the dynamism of the variables, particularly the pedagogy, learning media, spaces, learners themselves and the study location. However, exploring the intermediate space as physical informal learning environment that affect students’ performance and satisfaction in higher education remain crucial and decisive among educators and researchers. Therefore, there is a growing interest in higher education institutions, nationally and internationally, in the creating of new types of learning environment supporting learnercentered or constructivist pedagogy. Hence, The Next Generation Learning Spaces project team (NGLS) under Australian Learning & Teaching Council ( The University Of Queensland) , explored the interdependence of pedagogy, space, and technology to develop the Pedagogy-Space-Technology (PST) framework which permits institutions to develop new teaching and learning setting that will strengthen student engagement and enhance learning outcomes. This paper contributes to the paramount significance of the quality informal learning environment in order to accomplish functional obligation and cater for learner’s emotional urgency for enthusiasm and touch of identity.